2020
DOI: 10.1111/and.13546
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sperm telomere length and sperm quality in infertile men

Abstract: Telomeres, noncoding and repetitive DNA sequences play a significant function in chromatin integrity. Telomere length is age-dependent in somatic cells, while it increases in sperm cell with age. Therefore, we aimed to assess sperm chromatin, leucocyte and sperm telomere length (LTL, STL) in spermatozoon of 38 infertile and 19 fertile men aged between 20 and 50 years. Protamine deficiency (chromomycin A3 test), DNA fragmentation (TUNEL assay), lipid peroxidation (Bodipy probe) and telomere length (quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 43 publications
6
37
0
Order By: Relevance
“…This study used TUNEL and CMA3 staining to assess DNA fragmentation and protamine deficiency in sperm cells respectively. In line with other studies (Darmishonnejad et al., 2020; Rocca et al., 2016; Tahamtan et al., 2019), our finding showed a high level of DNA fragmentation and protamine deficiency in men with oligozoospermia.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study used TUNEL and CMA3 staining to assess DNA fragmentation and protamine deficiency in sperm cells respectively. In line with other studies (Darmishonnejad et al., 2020; Rocca et al., 2016; Tahamtan et al., 2019), our finding showed a high level of DNA fragmentation and protamine deficiency in men with oligozoospermia.…”
Section: Discussionsupporting
confidence: 93%
“…In line with other studies (Darmishonnejad et al, 2020;Rocca et al, 2016;Tahamtan et al, 2019), our finding showed a high The telomere in spermatozoa is a repetitive sequence that protects the chromosome terminal from both endogenous and exogenous damage (Von Zglinicki, 2002). So it is more likely that shortened sperm telomere may contribute to sperm DNA damage in oligozoospermic individuals.…”
Section: Discussionsupporting
confidence: 91%
“…Another layer of complexity in the aetiology of male infertility is due to the role of telomeres [25][26][27][28][29][30][31], with several studies investigating sperm telomere length (STL) and leukocyte telomere length (LTL) in male infertility [26,29,[31][32][33][34][35]. These studies have been conducted using different study designs, measuring techniques, exposure variables and outcomes, and have a limited sample size, ranging from 20 to 100 in Caucasian males.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our study did not find evidence of any correlation between TL in the male pronucleus and such parameters of sperm quality as concentration, progressive motility or normal morphology. While some studies registered correlations between TL in spermatozoa and total sperm count [ 54 , 55 ], sperm concentration [ 56 ], motility [ 57 , 58 ], sperm DNA fragmentation [ 57 , 58 ] and oligozoospermia [ 54 ], other studies did not show such associations [ 30 , 55 , 57 , 58 ]. There is a possible explanation for such discrepancies in the results.…”
Section: Discussionmentioning
confidence: 99%